2023
DOI: 10.1002/gj.4789
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of oil–water contact within Tipam reservoir: A study from Upper Assam Basin, North‐East India

Abstract: Fluid contacts within a reservoir can vary either because of compartmentalization by faults, lithological variations, hydrocarbon fill history or changes in the hydrodynamic activity of fluids. Their detailed interpretation is significant for estimating potential reserves and developing an explored hydrocarbon field. This study uses high‐quality three‐dimensional (3D) seismic reflection data to decipher the fluid contact zones and their types from the well‐known Tipam reservoir in the petroliferous Upper Assam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…and elsewhere in similar depositional settings Kumar et al (2023a). use high-quality three-dimensional (3D) seismic reflection data to decipher the fluid contact zones and their types from the well-known Tipam reservoir in the petroliferous Upper Assam foreland basin; thus, potential clues to favourable reservoir types have been obtained.3 | PETROLEUM GEOCHEMISTRYHakimi, Abass, et al (2023) studied the physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequences of the Melut Basin, southern Sudan, to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity.According to the biomarker maturity indicators, they revealed that most of the Melut Basin's oils were generated in the main stage of oil generation, exhibiting a range of peak mature to late mature.…”
mentioning
confidence: 97%
“…and elsewhere in similar depositional settings Kumar et al (2023a). use high-quality three-dimensional (3D) seismic reflection data to decipher the fluid contact zones and their types from the well-known Tipam reservoir in the petroliferous Upper Assam foreland basin; thus, potential clues to favourable reservoir types have been obtained.3 | PETROLEUM GEOCHEMISTRYHakimi, Abass, et al (2023) studied the physical and geochemical characteristics of crude oil samples representing the Cretaceous and Palaeogene reservoir sequences of the Melut Basin, southern Sudan, to gain information about source rock properties, including organic matter characters, depositional environment and thermal maturity.According to the biomarker maturity indicators, they revealed that most of the Melut Basin's oils were generated in the main stage of oil generation, exhibiting a range of peak mature to late mature.…”
mentioning
confidence: 97%